Transient left bundle branch block and left ventricular dysfunction in a patient with NLRP1-associated autoinflammation with arthritis and dyskeratosis syndrome. (25th January 2019) - Garrelfs, Mark R.; Hoppenreijs, Esther; Tanke, Ronald B.
Abstract: The NLRP1-associated autoinflammation with arthritis and dyskeratosis syndrome is a rare novel autoinflammatory disorder. Cardiac involvement has not been previously reported. We present a 12-year-old girl with NLRP1-associated autoinflammation with arthritis and dyskeratosis syndrome who was diagnosed with severely impaired left ventricular function and complete left bundle branch block during an exacerbation of the disease. Cardiac dysfunction proved to be rapidly reversible after initiation of high-dose methylprednisolone.